International Management: Culture, Strategy, and Behavior - Fred Luthans; Jonathan Doh (New York McGraw Hill, 2021)
Changes in the global business environment continue at an accelerated pace. The challenges for international management reflect this dynamism and the increasing unpredictability of global economic and political events. The challenge in today's uncertain geopolitical and economic environment is to learn and effectively practice international management. Past assumptions must always be tested and challenged, and best practices will continuously evolve in response to changing environmental and competitive conditions. Those with the knowledge and skills to apply the contents of this text on international management will be taking a huge step toward gaining a competitive advantage over those who do not have such a perspective. They will be in a strong position to gain a broad understanding and to take specific steps for implementation of effective managing across cultures.In the seventh edition of International Management, Luthans and Doh have taken care to retain the effective foundation gained from research and practice over the past decades. At the same time, they have fully incorporated important new and emerging developments that have changed what international managers are currently facing and likely to face in the coming years. Of special importance is that students of international management understand what will be expected of them from the range of stakeholders with whom they interact.
Keywords: Business; Management; International Business and Management (ECO2023-N )